Analisis Penyajian Konsep dan Soal pada Lembar Kerja Siswa (LKS) Matematika SMK Kelas X Terbitan Cahaya Mentari, Surakarta - Sudiyah Anawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2011)
:This study aimed at analyzing the presentation of concepts and questions on theworksheet vocational high school students firt class a semester publications Cahaya Mentari. Methods of research using qualitative descriptive methods, in this study the authors did not conduct experiments or field research. Method used is literature study method in accordance with references from varioussources related dengnan issues to be addressed. Population taken in this study are the concepts and issues urian short and multiple choice, to serve as study sample. Review the concept based on common benchmark compilation of textbooks, while the review examined a matter of using the rules about the presentation in the form ofdescriptions and multiple choice according to the study of materials, construction andstudy of language.